2017
DOI: 10.1007/s10549-017-4120-0
|View full text |Cite
|
Sign up to set email alerts
|

Utilization trend and regimens of hypofractionated whole breast radiation therapy in the United States

Abstract: Purpose We aimed to evaluate the adoption of hypofractionated whole breast irradiation (HF-WBI) over time and factors related to its adoption for patients undergoing lumpectomy. We also examined whether HF-WBI can increase the overall use of radiotherapy. Methods Using data from the National Cancer Database between 2004 and 2013, we identified 528,051 invasive and 190,431 ductal carcinoma in situ (DCIS) patients who underwent lumpectomy. HF-WBI was defined as 2.5-3.33 Gy/fraction to the breast, whereas conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…A study by Prades et al (n = 34 859) reported 6.7% of patients received HFRT in 2005 compared with 29.0% in 2015 in all breast cancer patients in Catalonia. In a study by Hasan et al (n = 528 051), HFRT in the United States for post‐BCS early‐stage invasive breast cancer patients was only 15.6% in 2013, although a substantial increase from 0.7% in 2004. The use of HFRT in this patient population can still be considered low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Prades et al (n = 34 859) reported 6.7% of patients received HFRT in 2005 compared with 29.0% in 2015 in all breast cancer patients in Catalonia. In a study by Hasan et al (n = 528 051), HFRT in the United States for post‐BCS early‐stage invasive breast cancer patients was only 15.6% in 2013, although a substantial increase from 0.7% in 2004. The use of HFRT in this patient population can still be considered low.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, use of HFRT in 2015 for post‐BCS DCIS patients (73.4%) parallels that of invasive breast cancer patients (74.6%). In the United States, a study by Stokes et al (n = 101 615) reported trends of increased HFRT use in patients with DCIS from 4.3% in 2004 to 33.0% in 2014 and a study by Hasan et al (n = 190 431) reported increasing use of HFRT from 0.4% in 2004 to 13.4% in 2013. Current evidence suggests that HFRT use in patients with DCIS is safe; however phase III randomized trials such as the Trans‐Tasman Radiation Oncology Group (TROG) DCIS trial which has not yet been published may strengthen the level of evidence supporting this practice and potentially lead to increased HFRT use.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2013, the ASTRO Choosing Wisely Campaign has endorsed considering HF-WBI for such women, 5 but adoption has been slow in the United States. [6][7][8][9] Reticence to embrace HF-WBI has included concerns about the effect of this treatment regimen on cosmesis, particularly when used with a tumor bed boost or in patients who receive chemotherapy or with larger breast size.…”
Section: Introductionmentioning
confidence: 99%
“…Returning to the patterns-of-practice data, an important caveat to interpreting the results previously discussed is that patient characteristics may not have be similar between the groups treated with hypofractionated vs. conventional radiation. Using the same National Cancer Database (NCDB) as Stokes et al ( 16 ) and Zhong et al ( 18 ), Hasan et al ( 42 ) found that hypofractionation was used more commonly in older patients (2.6% age <40 vs. 19.5% age >80; RR 8.40, 95% CI 5.01–14.09), those with node-negative disease (9.8% pN0 vs. 3.3% pN1; RR 0.38, 0.36–0.40), smaller tumors (9.5% ≤ 2.0 cm vs. 5.9% 2.1–5.0 cm; RR 0.78, 0.75–0.81), and lower-grade cancers [10.9% Grade 1 vs. 9.1% Grade 2 (RR 0.87, 0.85–0.90) vs. 5.8% Grade 3 (RR 0.79, 0.76–0.83)]. However, a survey of 2,150 randomly selected members of the American Society for Radiation Oncology suggests that the decision to forgo boost may still be made solely on the basis of WBI fractionation schedule.…”
Section: Fractionation Schedulementioning
confidence: 99%